Pengantar Hukum Internasional: Prinsip, Sumber, dan Peranannya Dalam Dunia Modern - Syamsuddin, Muh Suharto; Dewi, Mira Nila Kusuma; Hidayat, Rian; A, Amrullah; Octaviany, Resty (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
International law is a complex and dynamic normative framework that regulates relations among states, international organizations, and other legal subjects at the global level, emphasizing fundamental principles such as state sovereignty, non-intervention, the prohibition of the use of force, and human rights. This article provides an in-depth analysis of the definition, scope, history, sources, key principles, and the role of international organizations in the context of contemporary challenges, including climate change, cybersecurity, terrorism, migration, and geopolitical conflicts. Using historical, analytical, and case-study approaches, including the 2022 Russian invasion of Ukraine, the author explores the evolution of international law from the 17th century to the current digital era. The main findings indicate that although international law promotes global stability and cooperation, its effectiveness is often undermined by unequal enforcement, the realpolitik of powerful states, and gaps in emerging norms for new issues. This article contributes to the international law literature by advocating structural reforms, such as strengthening enforcement mechanisms and integrating technology, to address 21st-century challenges.